Over-the-Scope Clip Applications as First-Line Therapy in the Treatment of Upper Non-variceal Gastrointestinal Bleeding, Perforations, and Fistulas - Qiu, Jiayu; Xu, Jun; Zhang, Yanxia; Liao, Foqiang; Zhu, Zhenhua; Shu, Xu; Chen, Youxiang; Pan, Xiaolin (Frontiers in Medicine, 2022)
Background The over-the-scope clip (OTSC) is an innovative device and has been successfully used in endoscopic treatment, however, there is a lack of clinical data from China. The aim of this study is to investigate the OTSC applications in the treatment of upper non-variceal gastrointestinal bleeding (UNVGIB), perforations, and fistulas in China. Methods In total, 80 patients were treated with one OTSC respectively as first-line therapy in our endoscopy center between January 2016 and November 2020. Among them, 41 patients had UNVGIB, 34 patients had perforations, and five patients had fistulas. The technical and clinical success rates were used to assess the efficacy of OTSC on the above diseases. In addition, we compared the hemostatic efficacy of OTSC with the standard endoscopic therapy in ulcer bleeding and Dieulafoy's lesion by propensity score matching analysis. Results In general, the OTSCs were applied successfully in all patients and achieved 100% (80/80) technical success. The clinical success of all patients was 91.3% (73/80). Among 41 patients with UNVGIB, the clinical success was 85.4% (35/41); 6 patients presented with recurrence. For patients of Dieulafoy's lesion and under antithrombotic therapy, we found that OTSC treatment had both efficient and reliable hemostasis effects. In addition, according to the characteristics of ulcers, site of bleeding lesion, and Blatchford score, all patients received similar and reliable clinical success rates. After propensity score matching, we found that OTSC treatment had low rebleeding rates when compared with standard endoscopic therapy in both Dieulafoy's lesion (15.0 vs 30.0%) and ulcer bleeding (17.6 vs 29.4%). Among 34 patients with perforations, the clinical success was 100% (34/34). Among five patients with fistulas, only one patient failed in maintaining the OTSC before esophageal fistula healing, and the clip achieved an overall clinical success of 80% (4/5). Conclusion The OTSC represents a safe and effective endoscopic therapy for UNVGIB, perforations, and fistulas as first-line treatment, especially for Dieulafoy's lesion or patients under antithrombotic therapy for UNVGIB, etc. However, OTSC application in these specific lesions or patients lacks adequate evidence as first-line treatment. Therefore, further larger sample and multi-center clinical trials are required to improve its indications in clinical treatment.